Evaluating the Use of Very High-Resolution RGB Imagery from UAV for Vegetation Classification - Krátký, Martin; Komárková, Jitka (IEEE (Institute of Electrical and Electronics Engineers), 2023)
The article explores using very high-resolution RGB data from unmanned aerial vehicles (UAVs) to explore the possibilities of utilizing data to monitor vegetation. The Baroch nature reserve, located in the Pardubice region of the Czech Republic, is used as an area of interest. Data is collected using the UAV DJI Mavic 2 DUAL Enterprise. The reserve is overgrown mainly with reed and cattail and is used as a pasture. The paper aims to determine the effectiveness of utilizing UAV technology and very high-resolution RGB data to identify, monitor, and classify vegetation types in this grassy habitat and to provide insights into the practicality of using such data for ecological research and landscape management purposes.
Hodnocení využití RGB snímků s velmi vysokým rozlišením z bezpilotních letounů pro klasifikaci vegetace
Keywords: UAV; Data Processing; Supervised Classification; Unsupervised Classification; RGB Data; UAV; zpracování dat; řízená klasifikace; neřízená klasifikace; RGB data